IL23R is a Pathogenic Gene in Type 1 Regulatory T cells During Mouse Cardiac Transplantation Models. (July 2018) - Gu, Guangxiang; Lu, Tianfei; Xu, Ning; Xia, Qiang
Abstract : IL23R has been confirmed to be a pathogenic gene in Th17 cells. However, its role in type 1 regulatory T cells (Tr1 cells) is not clear, especially in the field of transplant tolerance induction. First, we generated mouse heart transplantation model in wt and IL23R ko mice and the results showed that the allograft survival was prolonged in IL23R ko mice group. To test the function of IL23R on Tr1 cells, we did wt and il23r ko Tr1 cells adoptive transfer in mouse heart transplantation models and found that both wt and il23r ko Tr1 cells could prolong the allograft survival, but the survival time was much longer in IL23R ko group than that in wt Tr1 group. Next, we differentiated the wt and Il23r ko Tr1 cells by cultured with IL-27, and no difference of IL10 expression was found between the two groups. Further nano-string results showed IL23Rko Tr1 cells expressed more inhibitory surface markers such as PD-1, Tim-3, Tigit and transcription factors such as prdm1, ahr, irf1.our results showed that IL23R ko Tr1 cells. To better understand the inhibitory function of il23r ko Tr1 cells on effect T cells, we co-cultured the Tr1 cells with effect T cells, and found that il23r ko Tr1 cells could better inhibit IFN-g, TNF-a and IL-17 expression. Based on our findings, IL23R was pathogenic gene that could inhibit the Tr1 cell function. Knockout of IL23R in Tr1 cells could better prolong the allograft survival in the mouse heart transplant tolerance induction models.